Characterization of nanocrystalline anatase titania: an in situ HTXRD study - Jagtap, Neelam; Bhagwat, Mahesh; Awati, Preeti; Ramaswamy, Veda (Thermochimica Acta, 2005)
Nanocrystalline titania was synthesized by the hydrolysis of titanium iso-propoxide using ultrasonication. The powder XRD patterns of the sample were recorded in static air and vacuum using a Philips X-pert Pro diffractometer equipped with a high-temperature attachment (HTK16) from room temperature (298 K) to 1173 K and were analyzed by the Rietveld refinement technique. The anatase to rutile phase transformation was observed at 1173 K for the data collected in static air. Only 3% of anatase titania transformed to rutile when the experiments were carried out at H 73 K in vacuum. The phase transformation from anatase to rutile is accompanied by a continuous increase in the crystallite size of the anatase phase from 9 nm at room temperature to 28 nm at 873 K and then to 50 nm at 1173 K in air while the process of crystallite growth was suppressed in vacuum. A linear increase in the unit cell parameters `a' and `c', and thus, an overall linear increase in the unit cell volume was observed as a function of temperature in static air as well as vacuum. The lattice and volume thermal expansion coefficients (TEC), alpha(a), alpha(c), and alpha(v) at 873 K are 8.57 x 10(-6), 8.71 x 10(-6) and 25.91 x 10(-6) K-1 in air and 18.01 x 10(-6), 14.95 x 10(-6) and 51.13 x 10(-6) K-1 in vacuum, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Anatase; HTXRD; Rietveld refinement; rutile; thermal expansion coefficient; titania

Cu-Ce mixed oxides supported on Al-pillared clay: effect of method of preparation on catalytic activity in the preferential oxidation of carbon monoxide - Ramaswamy, Veda; Malwadkar, Sachin S.; Chilukuri, Satyanarayana V. (Applied Catalysis B-Environmental, 2008)
The possibility of using Al-pillared montmorillonite (Al-PILC) clay as a high-surface-area support for CuO-CeO2-based catalysts has been investigated. The preparation of the samples was done by three different methods, viz., amorphous citrate route (ACR), deposition precipitation (DP) and wet impregnation method (WIM). Samples with different CuO-CeO2 loadings (10-50 wt.%) were prepared by each of the three methods. The catalytic activity of these samples was investigated for the preferential oxidation (PROX) of carbon monoxide (CO) in excess of H-2. The samples prepared by DP and WIM methods show better activity than the samples prepared by ACR method. At low Cu content, the samples prepared by DP method have a slight edge over samples prepared by WIM method. The DP-30 sample shows a very high CO conversion of 96.1% at 423 K. A higher dispersion of CuO-CeO2 on pillared montmorillonite clay and better reducibility of copper oxide species may be responsible for the good activity of these samples even at lower reaction temperatures. A higher O-2/CO ratio increased the CO conversion but led to a reduction in oxidation selectivity. No methanation of CO or CO2 was observed at the reaction temperature. These CuO-CeO2/Al-PILC samples could be considered as comparable in performance with supported noble metal catalysts for the preferential oxidation of CO in excess hydrogen. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alumina-pillared clay; Clay-supported CuO-CeO2; CuO-CeO2; PROX of CO